Strategi Desain Produk Menggunakan Konsep Nirmana Dwimatra: Implementasi dalam Proses Pembelajaran pada Mahasiswa Desain Produk FIK Telkom University - Husen Hendriyana; Martiyadi Nurhidayat; Wuri Handayani (Institut Seni Indonesia Denpasar, 2022)
This article is the result of designed research, and the writing is based on the practice-led research paradigm. This research's case study and background are based on classroom action research, specifically in the practice of 2D visual design. This design-practice study aims to provide models of creativity that can enrich the creative processes of similar designs with processes that are different from the existing ones. This work is created using the applicative approach of the Elementary Drawing Form, also known as Nirmana. To achieve the specified goals, the practice design method was carried out in four stages: understand (object & subject), exploration and experiment, define (point of view), ideate, prototype, and feasibility test. This Nirmana-dwimatra-inspired product design incorporates design fundamentals and principles to produce a valuable and meaningful work of design. This study affords models of creative processes based on a practice-led research instrument and indicator with aesthetic, artistic, and skill as its foundation.